Plasma biomarkers contribution to the structural alteration of perivascular spaces in Alzheimer's disease. (20th December 2022) - Sibilia, Francesca; Sheikh‐Bahaei, Nasim; Mack, Wendy J; Choupan, Jeiran
Abstract: Background: Perivascular spaces (PVSs) are fluid‐filled spaces in the brain surrounding blood vessels. Their function is to facilitate the cerebrospinal fluid (CSF) drainage between the interstitial space and the blood vessel space, allowing the outflow of waste soluble proteins in the brain. Aging leads to the increase of PVS number and volume, especially in basal ganglia and centrum semiovale. Stress was found to alter the cerebral flow of metabolites in the brain and to accelerate Aβ accumulation. High level of cortisol causes hypertension, contributing to increase of blood pressure. Angiotensin‐II raises arterial blood pressure quickly, and its production is associated to levels of Angiotensin‐converting enzyme (ACE). This study objective is to investigate the relationship between plasma biomarkers and the PVS volume fraction, and their effect on cognitive impairment process. Method: Older adults from the ADNI‐1 population (n=108, age range= 56‐89 years old, http://adni.loni.usc.edu ), were divided into healthy control, mild cognitive impairment (MCI) and Alzheimer's (AD) patients. MRI T1w images were acquired at 3T for all participants. PVS volume fraction was obtained by using parcellation and quantitation within white matter volume at global and regional levels. Linear regressions were run considering PVS volume fraction as dependent variable, calculated both in the total white matter and in the basal ganglia. Levels of cortisol, ACE and matrix metallo‐proteinases (MMPs) 2 and 9 were treated as independent variables. Pulse, age, sex, apolipoprotein E4, and diagnosis were included as covariates. Result: A main effect of MMP‐9 was seen on the PVS of the total white matter (p=0.046), with the covariates age and diagnosis showing a significant effect. Mediation analyses showed that diagnosis was the factor leading such relationship (p<0.05). PVS in the basal ganglia had a trend of being significantly associated to decreases of MMP‐2 (p=0.052). No significant effect was seen between PVS and cortisol, nor ACE. Conclusion: This study shows for the first time that there is a significant relationship between higher levels of MMP‐9 and alterations in PVS, when considering the cognitive impairment in older adults. This confirms previous findings that associated increase levels of MMP‐9 to faster Aβ accumulation.